Os programas eleitorais das europeias de 2014: uma análise preliminar das principais dimensões de competição - José Santana Pereira (2014)
The European project has enjoyed a substantive support from both elite and masses in Portugal. Since the country joined the ECC, in 1986, the main political parties have been strong supporters of Europe. In recent years, however, political and economic crises have undermined the support for the European project. In this paper we produce a preliminary analysis of the competition dimensions in the 2014 European elections. We empirically analyze the position of the five most important Portuguese political parties towards European integration, the Euro, debt renegotiation, Eurobonds, and changes in pensions in a context that fosters contestation of European integration and its outputs.